Mindfulness and Emotion Regulation in Adolescents and Young Adults with Cancer: A Qualitative Systematic Review - Maesaroh; Maulana, Herdiyan; Rangkuti, Anna Armeina (Journal of Educational, Health and Community Psychology, 2025)
Adolescents and young adults (AYA) with cancer frequently experience emotion dysregulation, yet existing reviews have focused mainly on symptoms such as anxiety, depression, or quality of life. This systematic literature review examined how mindfulness-based interventions (MBIs) support emotion regulation in AYA with cancer. Following PRISMA 2020 guidelines, we searched PubMed, Scopus, Web of Science, PsycINFO, and Google Scholar for studies published between 2015 and 30 June 2025 in English or Indonesian. Eligible studies involved AYA aged 10–39 years with a current or past cancer diagnosis, delivered an MBI, and reported emotion regulation or closely related outcomes. Two independent reviewers screened records, appraised methodological quality using design-appropriate tools (e.g., CASP/MMAT, RoB-2, JBI), and resolved discrepancies by consensus. Because of substantial heterogeneity in designs, interventions, and measures, data were synthesized using thematic meta-synthesis (qualitative) and narrative synthesis with vote-counting by direction of effect (quantitative). From 2,562 records, 10 studies met the inclusion criteria. Across designs, MBIs consistently enhanced emotional awareness, acceptance of difficult feelings, and self-regulatory coping; several trials also reported reductions in distress and improvements in self-compassion, although quantitative findings on emotion regulation difficulties were mixed. Limitations include small sample sizes, heterogeneous interventions and measures, and lack of protocol registration. Overall, MBIs show promising potential to strengthen emotion regulation in AYA with cancer, but larger, rigorously controlled trials with standardized emotion regulation outcomes and longer follow-up are needed.